EXPERTISE AS ONE OF THE BASIC FEATURES OF CONCEPTUAL SPHERE (BASED ON THE MATERIAL OF THE ENGLISH POPULAR SCIENCE PEDAGOGICAL DISCOURSE) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-1-95-103The article is devoted to the cognitive discourse analysis of the conceptual sphere of the English popular science pedagogical communication. The purpose of the analysis is to study and describe the linguistic representation of expertise as one of the key features of the conceptual sphere. On the material of English popular science pedagogical magazines, it is revealed that in the conceptual sphere of the English popular science pedagogical discourse, the feature of expertise is responsible for providing the audience with empirically defined pedagogical principles and teaching methods. In addition, the feature of expertise shows the expert knowledge and experience as well as serves as a tool for forming a trusting relationship between the professional pedagogical community and its audience.The results of the study show that in the English popular science pedagogical discourse, the feature of expertise is verbalised with the help of such speech mechanisms as so-called formula statements which represent indisputable facts about the way students should be taught; names of official documents testifying to the knowledge of teachers about educational laws; lexemes showing empiricality of information; lexemes indicating the quality and frequency of an action; stylistic enumeration.Key words: discourse, pedagogical communication, conceptual sphere, popular science discourse, popular science pedagogical discourse, the features of a conceptual sphere